2021
DOI: 10.1140/epjc/s10052-021-09491-0
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the anisotropy of the Universe with the X-ray and UV fluxes of quasars

Abstract: We test the anisotropy in the Finslerian cosmological model with the X-ray and ultraviolet (UV) fluxes of quasars. The 2015 and 2020 compilations of quasars are used in the cosmological constraints. We find that the dipole direction given by the 2015 quasar compilation is not far away from the one provided by the Pantheon sample and the angular differences are around $$30^{\circ }$$ 30 ∘ . The Pantheon sample is combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…3.2.1 (e.g. López-Corredoira et al 2016;Bisogni et al 2017;Lusso et al 2019b;Melia 2019;Wei and Melia 2020;Demianski et al 2020;Zhao and Xia 2021;Li et al 2021a;Bargiacchi et al 2021a;Leizerovich et al 2021). Amongst the main results, it has been found that the expansion rate of the Universe based on the combined quasar and supernovae Ia Hubble diagram shows a deviation from the concordance model at high redshifts (z [ 1:4), with a statistical significance of $ 3 À 4r.…”
Section: Main Results and Forecastsmentioning
confidence: 97%
“…3.2.1 (e.g. López-Corredoira et al 2016;Bisogni et al 2017;Lusso et al 2019b;Melia 2019;Wei and Melia 2020;Demianski et al 2020;Zhao and Xia 2021;Li et al 2021a;Bargiacchi et al 2021a;Leizerovich et al 2021). Amongst the main results, it has been found that the expansion rate of the Universe based on the combined quasar and supernovae Ia Hubble diagram shows a deviation from the concordance model at high redshifts (z [ 1:4), with a statistical significance of $ 3 À 4r.…”
Section: Main Results and Forecastsmentioning
confidence: 97%
“…The best way to test this is to use alternate cosmological probes. Some work has already been done in this direction and it includes the use of HII starburst galaxy observations which extend to redshift 𝑧 ∼ 2.4 (Mania & Ratra 2012;Chávez et al 2014;González-Morán et al 2019Cao et al 2020Cao et al , 2021cJohnson et al 2021;Mehrabi et al 2022), quasar (QSO) angular size measurements which probe to 𝑧 ∼ 2.7 ★ E-mail: nkhadka@phys.ksu.edu † E-mail: mmary@cft.edu.pl ‡ E-mail: zajacek@mail.muni.cz § E-mail: bcz@cft.edu.pl ¶ E-mail: ratra@phys.ksu.edu (Cao et al 2017;Ryan et al 2019;Cao et al 2020Cao et al , 2021dZheng et al 2021;Lian et al 2021), QSO X-ray and UV flux measurements which reach to 𝑧 ∼ 7.5 (Risaliti & Lusso 2015Khadka & Ratra 2020aYang et al 2020;Lusso et al 2020;Zhao & Xia 2021;Li et al 2021a;Lian et al 2021;Rezaei et al 2021;Luongo et al 2021) 1 , and gamma-ray burst (GRB) data that extend to 𝑧 ∼ 8.2 (Wang et al 2016(Wang et al , 2021Fana Dirirsa et al 2019;Amati et al 2019;Khadka & Ratra 2020c;Demianski et al 2021;Luongo et al 2021;Hu et al 2021;Luongo & Muccino 2021;Cao et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Farooq et al 2017;Scolnic et al 2018;Planck Collaboration 2020;eBOSS Collaboration 2021). The measurements, however, are not yet decisive enough (see, surements that reach to z ∼ 7.5 (Risaliti & Lusso 2015Khadka & Ratra 2020a,b, 2021Lusso et al 2020;Zhao & Xia 2021;Rezaei et al 2022;Luongo et al 2021;Leizerovich et al 2021;Colgáin et al 2022;Dainotti et al 2022a), 1 and -the main subject of our paper -gamma-ray burst (GRB) observations that reach to z ∼ 8.2 (Cardone et al 2009(Cardone et al , 2010Samushia & Ratra 2010;Dainotti et al 2013;Postnikov et al 2014;Wang et al 2015Wang et al , 2016Dainotti & Del Vecchio 2017;Dainotti & Amati 2018;Wang et al 2022;Fana Dirirsa et al 2019;Amati et al 2019;Khadka & Ratra 2020c;Hu et al 2021;Demianski et al 2021;Khadka et al 2021b;Luongo et al 2021;Luongo & Muccino 2021;Cao et al 2021a;Liu et al 2022). In this paper the highest redshift GRB we use is at z = 9.4 (Cucchiara et al 2011), but GRBs might be detectable to z = 20 (Lamb & Reichart 2000).…”
Section: Introductionmentioning
confidence: 85%